¿Responden los micromoluscos a los cambios ambientales durante el Holoceno tardío en el sur del mar Caribe colombiano? (2014)
ABSTRACT: Holocene environmental changes in the southern Caribbean Sea and their implications on the composition of marine micro and malacofauna are unknown. We embarked an oceanographic expedition aboard the ship, ARC-Quindío of the Colombian Navy, to drill at three sites in the Gulf of Urabá using a platform gravity corer. To find possible correlations with paleoenvironmental changes during the late Holocene in the Gulf, we assessed the taxonomic composition (organic matter and calcium carbonate) and micromollusc abundance. The elevated richness and abundance of micromolluscs yields more calcium carbonate and less organic matter and answers to environmental changes in the late Holocene. We were able to define two contrasting environments in the Gulf of Urabá during the last 2800 years; an earlier environment dominated by marine waters and a more recent environment of a mixture of waters dominated by estuarine waters.